Environmental severity promotes phylogenetic clustering in campo rupestre vegetation - Miazaki,Angela S. (2015)
The stress-dominance hypothesis postulates that the importance of competition in plant communities declines with increasing environmental stress while the importance of environmental filters increases. To test this hypothesis for campo rupestre vegetation, we analyzed phylogenetic diversity and community structure of angiosperm communities at two study sites within the Itacolomi State Park, Minas Gerais, Brazil. Plots representing more favorable habitats, such as those with a higher percentage of rocky outcrops that might permit the tapping of deeper water and nutrient resources as well as higher contents of clay and loam thereby increasing water and nutrient availability, show higher phylogenetic diversity and therefore lower phylogenetic clustering than plots with more sever habitats. This observation is consistent with the stress-dominance hypothesis if we assume ecological niches to be conserved within evolutionary niches. However, more comprehensive studies including tests for phylogenetic signal of ecological niches are necessary before generalizations for larger regions may be carried out.